A Critical Analysis of the Response of Ilorin Sufi Scholars to Anti-Sufi Uprising in the Seventies in Nigeria - Yusuph Dauda Gambari (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
Sufism has been trailed by different criticisms for a long period. Different Muslim communities across the Muslim world have experienced anti-Sufism drives but launched in Nigeria in the seventies as it was inaugurated and coordinated by Shaykh Abubakar Mahmud Gumi, who acted under the guise and influence of Wahhābiyya-Salafiyya. As a result, Sufis across communities started responding by either preaching or writing. Sufi scholars in Ilorin, a border community between the North and South, were among the early responders to anti-Sufism who took to writing. Therefore, this paper is a critical analysis of the contents of Rafḍ al-Shubuhāt, written as a response to anti-Sufi waves in the city. An exegetical method of research was adopted to determine the appropriateness of the Sufi scholars to the anti-Sufism campaign in the metropolis. The findings revealed that most of the Salafiyya’s claims are unfounded and lack the proof to establish their genuineness, while the responses of the Sufi are not only appropriate but are also laced with evidence from the Qur’an, Ḥadīth, and submissions of different scholars, some of whom were Salafiyya scholars. The book is therefore recommended for the defence of Sufism in contemporary times.Contribution: This study contributes to revealing the efforts to tackle the anti-Sufism movement initiated by Sufis scholars in Ilorin Nigeria, by writing a book entitled Rafḍ al-Shubuhāt, as a counter-opinion.